(3EOGQI GdHjFI fMh GdEfJGL GdCfXas - (3RcQjG(B, (3WGMhfs ((3GdbGgQI(B:s (3LeYjI GdecJH GdYQHj ddHMhK hGdHjFI(B,s, 2005)
(3GdHjFI hGdGjchdhLjI, GdGOGQI GdhGYjI ddehGQO, GdGOGQI GdHjFjI hOhQgG aj GfXGa GdHjFI(B.s
(3GdeQGLY U(B.317s
Keywords: (3GdEOGQI GdHjFjIs; (3GdHjFIs; (3MeGjI GdHjFIs